2009
DOI: 10.1143/jjap.48.010204
|View full text |Cite
|
Sign up to set email alerts
|

(NaxK0.98-xLi0.02)(Nb0.8Ta0.2)O3 Lead-Free Piezoelectric Ceramics

Abstract: Pattern printability was examined while varying the thickness of a multilayer mask blank by simulation. The variations were related to the total thickness and the monolayer thickness of 40 Si/Mo bilayers. Printability was evaluated by using the pattern edge contrast for a binary mask and an attenuated phase shift mask (att-PSM). The total thickness variation degrades pattern edge contrast with decreasing exposure energy on a wafer. The phase shift between multilayer and absorber on a mask differs depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…. The XRD result demonstrates that the NKLNT ceramics correspond to a pure tetragonal perovskite structure without any secondary phase, as in a previous report . The corresponding piezoelectric properties with the remnant polarization ( P r ), coercive field ( E c ) and piezoelectric coefficient ( d 33 ) were 13.3 μC/cm 2 , 1.3 kV/cm, and 280 pC/N, respectively, are indicated in Table .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…. The XRD result demonstrates that the NKLNT ceramics correspond to a pure tetragonal perovskite structure without any secondary phase, as in a previous report . The corresponding piezoelectric properties with the remnant polarization ( P r ), coercive field ( E c ) and piezoelectric coefficient ( d 33 ) were 13.3 μC/cm 2 , 1.3 kV/cm, and 280 pC/N, respectively, are indicated in Table .…”
Section: Resultssupporting
confidence: 80%
“…This result is in agreement with our XRD and FE‐SEM analysis, although it is generally in contrast to most previous studies of NKN‐based ceramics, where the orthorhombic phase was mainly found. The difference originates substantially from the Na + rich content (53 mol%) on A sites of the Li‐ and Ta‐modified NKN ceramics, leading to a phase transformation from orthorhombic to tetragonal, as discussed earlier by Kim et al …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The sintering temperature of K 0.5 Na 0.5 NbO 3 is close to its melting-point and consequently it is not easy to achieve a dense ceramic without liquid phase sintering (Wang and Li, 2012). It has been reported (Zhen and Li, 2007;Kim et al, 2009) that grain size and core-shell structures in such grains influence piezoelectric properties. The BF content is affecting the sintering temperature, for larger contents of BF the conditions don't favor formation of large cluster and the constituent grains are disintegrated, thereby showing smaller grains.…”
Section: Resultsmentioning
confidence: 99%
“…Appearance of liquid phase during sintering promotes the AGG behavior as well as secondary phase . Generally, grain growth is classified into two types: normal and abnormal (exaggerated) grain growth .…”
Section: Sintering Of Knn‐based Ceramicsmentioning
confidence: 99%